2013
DOI: 10.1007/s00221-013-3771-2
|View full text |Cite
|
Sign up to set email alerts
|

Time flies when we view a sport action

Abstract: Humans' time evaluation within the range of hundreds of milliseconds is often distorted, and time is judged as much longer than actually is. This consistent overestimation has been interpreted as an indicator of the threshold level for the sensitivity of the perceptuomotor system. The purpose of this study was to investigate how the perception of time, both in sub- and supra-second timescales, changes for elite athletes that are considered as individuals with highly developed motor perceptual capabilities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
3
12
1
Order By: Relevance
“…Regarding the bias results, most participants in the task showed a tendency to overestimate subsecond durations and underestimate suprasecond durations, which is consistent with the results of other studies (Chen et al 2014). This finding is a well-known phenomenon in the field of time perception, especially in the reproduction task, and scholars have already offered a reasonable explanation (Wearden & Lejeune 2007).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding the bias results, most participants in the task showed a tendency to overestimate subsecond durations and underestimate suprasecond durations, which is consistent with the results of other studies (Chen et al 2014). This finding is a well-known phenomenon in the field of time perception, especially in the reproduction task, and scholars have already offered a reasonable explanation (Wearden & Lejeune 2007).…”
Section: Discussionsupporting
confidence: 89%
“…However, previous research found that sports experts have a more precise and stable timing ability than nonathletes, and the results of a reduced AE ratio and CV for sports experts were not repeated in this research. For example, Chen et al (2014) found that compared with nonathletes, athletes had reduced AE ratios in subsecond time ranges and reduced CVs in both subsecond and suprasecond time ranges for both expertiserelated and non-expertise-related stimuli. Our results suggest that there were no differences among the different groups with regard to the CV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This appears to be 35 particularly important for sportive competition, given the key role of action anticipation, motor coordination and motor 36 synchronization for a successful sportive performance. The study by Chen et al (2014) provides support to this view, 37 documenting higher accuracy and lower variability in elite fencers asked to reproduce the duration of an image of 38 scrambled pixels. This study suggests that elite athletes may be equipped with a superior ability in detecting the 39 duration of visual stimuli, which might be related to their long-term sport training.…”
Section: Discussionmentioning
confidence: 83%